### Introduction: Solving 3x + 2 = 8

In this Instructible, I will show you how to solve the equation 3x + 2 = 8.

### Step 1: Step 1: Subtract

The first step is to subtract 2 from both sides of the equal sign:

3x + 2 = 8

-2 -2

Which leaves us:

3x = 6

### Step 2: Step 2: Divide

In Step 2, we divide both sides by the coefficient in front of x:

3x = 6

/3 /3

Which gives us:

x = 2

### Step 3: Step 3: Check Your Solution

In the final step, we will check our solution by plugging our answer back in to the original equation:

3(2) + 2 = 8

We simplify this according to PEMDAS

6 + 2 = 8

8 = 8

Since we get the same number on both sides, we know the solution x = 2 is correct!

### Be the First to Share

Did you make this project? Share it with us!

### Recommendations

### Micro:bit Contest

### 3D Printed Student Design Challenge

### Unusual Uses Contest

### Most Used Actions

\mathrm{simplify} | \mathrm{solve\:for} | \mathrm{expand} | \mathrm{factor} | \mathrm{rationalize} |

Our online expert tutors can answer this problem

Get step-by-step solutions from expert tutors as fast as minutes. Your first 5 questions are on us!

In partnership with

You are being redirected to Course Hero

Correct Answer :)

Let's Try Again :(

Try to further simplify

### Related

### Number Line

### Graph

### Examples

equation-calculator

3x-2

en

## Nonlinear equations

### Step by step solution :

### Step 1 :

#### Equation at the end of step 1 :

3x^{2}- 2 = 0

### Step 2 :

#### Trying to factor as a Difference of Squares :

Factoring: 3x^{2}-2

Theory : A difference of two perfect squares, A^{2} - B^{2} can be factored into (A+B) • (A-B)

Proof : (A+B) • (A-B) =

A^{2} - AB + BA - B^{2} =

A^{2}- AB + AB - B^{2} =

A^{2} - B^{2}

Note : AB = BA is the commutative property of multiplication.

Note : - AB + AB equals zero and is therefore eliminated from the expression.

Check : 3 is not a square !!

Ruling : Binomial can not be factored as the

difference of two perfect squares

#### Equation at the end of step 2 :

3x^{2}- 2 = 0

### Step 3 :

#### Solving a Single Variable Equation :

Solve : 3x^{2}-2 = 0

Add 2 to both sides of the equation :

3x^{2} = 2

Divide both sides of the equation by 3:

x^{2} = 2/3 =

When two things are equal, their square roots are equal. Taking the square root of the two sides of the equation we get:

x = ± √ 2/3

The equation has two real solutions

These solutions are x = ±√ = ±

### Two solutions were found :

x = ±√ = ±## Nonlinear equations

### Step by step solution :

### Step 1 :

#### Equation at the end of step 1 :

3x^{2}= 0

### Step 2 :

#### Solving a Single Variable Equation :

Solve : 3x^{2} = 0

Divide both sides of the equation by 3:

3x^{2} = 0

When two things are equal, their square roots are equal. Taking the square root of the two sides of the equation we get:

3x = ± √ 0

Any root of zero is zero. This equation has one solution which is 3x = 0

### One solution was found :

3x = 0## 2 3x to how solve

You're back in the phone. I understand that this is your job. But endless chimes take you away from me.

How To Factor Polynomials The Easy Way!The town consisted of a military zone (barracks, headquarters, a soldiers' canteen, a car park, etc. ) and a residential area (houses of. Officers and contract soldiers, a hostel, an officers canteen, a bathhouse, a house of culture, etc.

### Now discussing:

- American eagle plus size
- Movie sonic vs movie mario
- Faux greenery outdoor privacy panels
- 2007 infiniti g37 sedan horsepower
- What is repeated subtraction
- Steven universe discord server

Enthusiasm. Yes, and in sex I was inventive not for age and very active, but still only now I realized what the experience and desire of an adult woman is. Natasha's kiss turned me on to chaos, and I tried to rip off her jacket, but immediately received a hefty slap in the face: How dare you.

I am a married woman. The jacket must remain clean and not wrinkled.

**853**854 855